Multitemporal Detection of Urban Heat Island Dynamics Using Landsat 8 and GIS in Payakumbuh City, West Sumatra, Indonesia (2017–2024) - Yasa Palaguna Umar; Nazhmi Hariz; Muhammad Roil Bilad (Program Pascasarjana Universitas Sriwijaya, 2026)
Background: Urbanisation converts vegetated and agricultural land into impervious surfaces, reducing evapotranspiration and intensifying the Urban Heat Island (UHI). Payakumbuh City, West Sumatra, Indonesia, has undergone rapid built-up growth whose thermal consequences remain unquantified. Objective: This study identified the spatial and temporal dynamics of UHI in Payakumbuh City from 2017 to 2024 using Landsat 8 OLI/TIRS Collection-2 Level-1 imagery and GIS-based spatial analysis. Methods: Supervised land use/land cover (LULC) classification, NDVI, NDBI, and emissivity-corrected land surface temperature (LST) were computed in QGIS, and relationships were tested using Spearman and Pearson correlations, ANOVA with Tukey HSD, regression, and principal component analysis. The study covered the 75.44 km² administrative area of Payakumbuh City (0°11′–0°16′ S, 100°34′–100°41′ E). Results: Built-up land increased from 38.77% to 50.36% of the city area (+11.59 percentage points), while agricultural land fell from 50.67% to 40.06% (−10.61). Mean NDVI declined from 0.62 to 0.53 and mean NDBI rose from −0.29 to −0.24, while maximum LST increased from 31.85 °C to 34.03 °C (+2.18 °C). NDVI correlated negatively with LST (ρ = −0.43 to −0.59) and NDBI positively (ρ = 0.53 to 0.65), all p < 0.001. LST differed significantly among classes (ANOVA F(4,1095) = 1062.6, p < 0.001, η² = 0.80), with built-up warmest (29.8 °C) and water coolest (23.4 °C). UHI-affected area expanded from 18.93 km² (25.09%) to 22.39 km² (29.68%), a gain of 3.46 km² (+4.59%). Conclusion: Strengthening urban greening, protecting agricultural land, and controlling built-up expansion are recommended climate-sensitive planning strategies.